Taking on terrorism. (IEEE spectrum)
The 11th day of September 2001 began with a tragedy beyond comprehension. It ended in a cacophony of outrage, blame, and urgent questions. How could so few terrorists create death and destruction on so massive a scale? How could US intelligence services have been caught so off guard? Can technology help prevent such attacks in the future, or at least respond to them more effectively if they do occur? A year after the strikes, answers to these questions are finally starting to take shape. The focus here is on the use of technology as a pillar of future counter-terrorism-from the advanced screening equipment now being installed at airports around the world to the robust emergency communications systems that will link workers and officials after any future calamities. Although the attacks prompted a broad array of technology initiatives, some of the most significant have been in intelligence, airport baggage screening, postal monitoring, biometric identification, radio and television broadcasting, hardened emergency communications, and personal security.